Innovative lightweight materials using sugarcane ash and neem fiber epoxy matrix composite for sustainable applications - Thandavamoorthy Raja (Results in Engineering)
This study presents a novel eco-friendly composite material derived from agricultural waste, uniquely combining neem fiber and sugarcane ash (SCA) within an epoxy matrix for lightweight applications. While both neem fiber and SCA have been explored individually in bio-based composites, their specific integration in this formulation offers distinct advantages. Neem fiber contributes natural strength and antimicrobial properties, while SCA enhances thermal stability, creating a composite that is both durable and sustainable. The optimized sample (12 gs of SCA, labelled L8) exhibited impressive mechanical properties, with a tensile strength of 49.14 MPa and flexural strength of 49.91 MPa, highlighting its robust resilience. Thermogravimetric Analysis revealed a degradation onset at 170 °C and a residual mass of 15 % at 400 °C, underscoring the material's excellent thermal stability, with a Heat Deflection Temperature of 78 °C suitable for moderate thermal applications. Confocal Laser Scanning Microscopy demonstrated significant antibacterial efficacy, with L8 showing a 23 mm and 21 mm inhibition zone against Klebsiella proteus, and E.coli comparable to the 27 mm zone produced by streptomycin. Scanning Electron Microscopy confirmed the uniform dispersion of SCA particles, ensuring strong interfacial bonding. The combination of neem fiber and SCA in this composite offers a unique balance of strength, thermal resistance, and antimicrobial properties, making it an attractive, sustainable alternative for industries such as automotive, packaging, and healthcare. By utilizing agricultural waste, this composite not only reduces environmental impact but also provides a durable, antimicrobial solution for applications requiring lightweight, sustainable materials.